2001
DOI: 10.21236/ada401076
|View full text |Cite
|
Sign up to set email alerts
|

Health Professions' Retention-Accession Incentives Study Report to Congress (Phase 1: Compensation Comparison of Selected Uniformed and Private-Sector Health Care Professionals)

Abstract: This document represents the best opinion of CNA at the time of issue. It does not necessarily reoresent the opinion of th^-n^mrtment of the Navv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Given the pay-gap results of the first phase of our study [2], it is somewhat surprising that aggregate attrition/continuation did not change significantly during the 1990s. In that first phase, we found that the military-civilian pay gaps widened significantly from FY 1991 to FY 2000 for all of the 23 specialties.…”
Section: Fy97mentioning
confidence: 84%
See 4 more Smart Citations
“…Given the pay-gap results of the first phase of our study [2], it is somewhat surprising that aggregate attrition/continuation did not change significantly during the 1990s. In that first phase, we found that the military-civilian pay gaps widened significantly from FY 1991 to FY 2000 for all of the 23 specialties.…”
Section: Fy97mentioning
confidence: 84%
“…The first phase was a comparative analysis of compensation between uniformed and private-sector health care professionals at logical military career junctures [2,3,4]. This analysis was an essential first step because we needed to understand whether a militarycivilian pay gaps exists, how large it is, and at what career junctures to evaluate the effect of pay on retention during the second phase of this study.…”
Section: Approachmentioning
confidence: 99%
See 3 more Smart Citations